The SPLASH/ICPC integrity marathon in Ibadan, Nigeria: incidence and management of injuries and marathon-related health problems - Ogwumike, Omoyemi O (BioMed Central, 2013)
BACKGROUND: The growing interest in marathon runners and marathons in Nigeria has not been reflected in reports of injuries and other health problems associated with these events. This study therefore outlines the incidence of injuries, marathon-related health problems and delivery of physiotherapy at the maiden and second editions of the Splash 105.5 FM/ICPC Integrity Marathon in Ibadan city, south-west Nigeria in 2009 and 2010. METHODS: Using a data entry sheet, demographics and information on running experience, past and present injuries and other health problems reported en route and at the finish line by the runners were documented. The prevalence of injuries and other health problems reported by previous and first-time runners were compared. RESULTS: In both events, 16.3% and 17.2% of the runners respectively reported injuries with significant occurrence in first-time runners (p = 0.003 for 2009; p = 0.002 for 2010) mostly at the finish line. The reported injury type and site were muscle cramps and the thigh (39.7% and 76.4% respectively). Heat exhaustion was reported by 42.8% of runners in 2009 and 56.3% in 2010. Cryotherapy was mostly used in combination with other physiotherapy modalities in both years. CONCLUSION: Most of the injuries and other health problems were reported by first-time marathon runners mainly at the finish line. The most reported site of injury was the thigh while muscle cramps and heat exhaustions were the most reported types of injuries and health problems. First-time marathon runners should be adequately informed of the predisposition to injury during marathons and adequate body conditioning should be emphasized. Ample preparation and effective involvement of the physiotherapy team is essential for management of injured runners en route and at the finish line in a marathon.